A nickel-iron-based high-temperature alloy electrochemical polishing liquid and its preparation method and application

By preparing an electrochemical polishing liquid of nickel-iron-based high-temperature alloy containing a specific composition, the problem of lack of electrochemical polishing liquid suitable for nickel-iron-height alloy in the prior art is solved, and efficient polishing effect and long-life polishing are achieved liquid.

CN115404535BActive Publication Date: 2025-02-18HUANENG POWER INT INC +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211025745.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2025-02-18
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

The prior art lacks an electrochemical polishing liquid suitable for nickel-ferrothermal alloys, and the polishing liquid is prone to aging and has a short life after using a large amount of oxidative acids.

Method used

Provide a nickel-iron-based high-temperature alloy electrochemical polishing liquid, including phosphoric acid, hydrochloric acid, glycerol, ethylene glycol, ethanol, naphthalene sulfonic acid and butyndecyl glycol, and prepare stable electrochemicals through specific composition ratios and mixing sequences. Polishing liquid.

Benefits of technology

This electrochemical polishing liquid can effectively reduce the roughness of the surface of nickel-iron-based high-temperature alloy, improve the flatness and reflectivity of the surface, and has strong stability, is not easy to age, and has a long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115404535B_ABST
    Figure CN115404535B_ABST
Patent Text Reader

Abstract

This invention belongs to the field of electropolishing technology, specifically relating to an electrochemical polishing slurry for nickel-iron-based high-temperature alloys, its preparation method, and its application. In the electrochemical polishing slurry provided by this invention, naphthalenesulfonic acid, butynediol, ethanol, and specific polyols and acids are organically combined. Their synergistic effect can effectively polish high-temperature alloys, especially nickel-iron-based high-temperature alloys commonly used in high-temperature components of ultra-supercritical units, effectively reducing alloy surface roughness and improving surface smoothness and reflectivity. Notably, ethanol is not a conventional component in polishing slurries. This invention is the first to discover that the use of ethanol can promote the removal of air bubbles during polishing, increase polishing uniformity, and effectively reduce alloy surface roughness. Furthermore, the electrochemical polishing slurry provided by this invention exhibits strong stability, can be reused repeatedly, and is not prone to aging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic polishing, and specifically relates to a nickel-iron-based high-temperature alloy electrochemical polishing liquid and a preparation method and application thereof. Background Art

[0002] Coal-fired power generation generates electricity by generating high-temperature and high-pressure steam to drive the steam turbine. The higher the temperature and pressure of the steam, the higher the efficiency of power generation. According to the steam temperature and pressure parameters of the unit, it is divided into subcritical units, supercritical units, and ultra-supercritical units. In the field of coal-fired power generation, improving the parameters of thermal power generating units is of great practical significance for improving power generation efficiency, reducing harmful gas emissions, and achieving environmental friendliness and sustainable development.

[0003] Among the materials used for high-temperature components of ultra-supercritical units, nickel-iron-based high-temperature alloys are expected to be used in core components of power station boilers due to their advantages of easy processing and low price. However, the service environment of high-temperature components of units is very harsh, so in-depth research on the mechanical properties, organizational stability, deformation mechanism, and creep mechanism of alloys is the key to the safe and reliable operation of ultra-supercritical units. In the above research, high-quality metallographic samples need to be prepared. The surface defects, grooves, roughness, and cleanliness of metallographic samples will directly affect the accuracy of microstructure analysis.

[0004] Common surface leveling technologies include mechanical polishing, chemical polishing and electrochemical polishing. Mechanical polishing relies on physical means such as grinding, which has low polishing efficiency and easily forms a flowing metal layer on the surface, which cannot achieve the leveling effect. Chemical polishing relies on the slow dissolution of metal in chemical polishing liquid to achieve the polishing purpose, which has low efficiency and generally has large surface roughness, and cannot meet the requirements of microscopic analysis such as phase identification, phase distribution, grain boundary characteristics analysis, and orientation difference analysis of metallographic samples.

[0005] Compared with the first two polishing methods, electrochemical polishing technology relies on the different current densities of the convex and concave parts of the metal surface to achieve surface flatness. From a microscopic point of view, the surface of the sample is uneven, the convex part has a large current density and a faster dissolution rate; the concave part has a small current density and a slower dissolution rate, and finally the surface of the sample is flat and shiny. Electrochemical polishing has high efficiency, and the obtained sample surface has low roughness, no stress, and no deformation layer. Especially for products with complex shapes, the superiority of the process can be better demonstrated.

[0006] However, electrochemical polishing in the prior art is mostly applied to alloys that are more susceptible to corrosion, such as the electrochemical polishing of magnesium alloys, while high-temperature alloys (such as nickel-iron-based alloys) are relatively stable and the alloy surface is not easily corroded. The existing electrochemical polishing solution is not suitable for high-temperature alloys; in addition, for alloys whose surfaces are not easily corroded, a large amount of oxidizing acid is generally used, which will cause problems such as easy aging of the polishing solution and short life. Summary of the invention

[0007] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the prior art such as the lack of an electrochemical polishing liquid suitable for nickel-iron high-temperature alloys, as well as the defects of the electrochemical polishing liquid being easily aged and having a short life after using a large amount of oxidizing acid, thereby providing a nickel-iron-based high-temperature alloy electrochemical polishing liquid and a preparation method and application thereof. The electrochemical polishing liquid is particularly suitable for nickel-iron-based high-temperature alloy materials commonly used in high-temperature components of ultra-supercritical units.

[0008] To this end, the present invention provides the following technical solutions:

[0009] The present invention provides a nickel-iron-based high-temperature alloy electrochemical polishing solution, which comprises the following components by volume:

[0010] Phosphoric acid 20-60 parts; hydrochloric acid 1-3 parts; glycerol 1-30 parts; ethylene glycol 10-20 parts; ethanol 15-20 parts;

[0011] The electrochemical polishing solution also includes naphthalenesulfonic acid at a concentration of 0.02-1 g / L and butynediol at a concentration of 0.02-1 g / L.

[0012] Optionally, the nickel-iron-based high-temperature alloy electrochemical polishing solution comprises the following components by volume:

[0013] Phosphoric acid 40-60 parts; hydrochloric acid 2-3 parts; glycerol 18-30 parts; ethylene glycol 15-20 parts; ethanol 15-20 parts;

[0014] The electrochemical polishing solution also includes naphthalenesulfonic acid at a concentration of 0.03-1 g / L and butynediol at a concentration of 0.03-1 g / L.

[0015] Optionally, the mass concentration of the phosphoric acid is above 85wt%;

[0016] And / or, the mass concentration of the hydrochloric acid is above 37wt%.

[0017] Optionally, the viscosity of the electrochemical polishing liquid at 25° C. is 100-200 mP·s.

[0018] The present invention also provides a method for preparing the electrochemical polishing solution, comprising the following steps:

[0019] S1, mixing phosphoric acid and hydrochloric acid, adding naphthalenesulfonic acid and butynediol to obtain component A;

[0020] S2, adding glycerol and ethylene glycol to ethanol in sequence to obtain component B;

[0021] S3, mixing component A and component B, stirring to obtain the electrochemical polishing solution.

[0022] Among them, butynediol is solid and soluble in acidic solution, so it is first mixed with phosphoric acid and hydrochloric acid to help dissolve the additive; while the glycerol and ethylene glycol in component B have high viscosity and are easier to disperse evenly when added to ethanol.

[0023] Optionally, stirring is maintained during the mixing of component A and component B.

[0024] In addition, in the actual operation process, since the mixing of acid and other liquids will produce heat, they need to be added slowly. For example, the process can be controlled within a certain period of time, which can be controlled within about 1-2 minutes.

[0025] Optionally, the stirring time is 0.5-1h. The stirring process is conducive to the formation of macromolecular cross-linked structures of various components in the electrolytic polishing liquid through OH...O bonds, improving the stability of the polishing liquid, making it less likely to produce precipitates when placed for a long time, and improving the service life.

[0026] The present invention also provides an application of the electrochemical polishing liquid or the electrochemical polishing liquid prepared by the above preparation method in electrochemical polishing of nickel-iron-based high-temperature alloys;

[0027] It is particularly suitable for nickel-iron-based high-temperature alloy materials commonly used in high-temperature components of ultra-supercritical units.

[0028] The main constituent phases of the nickel-iron-based high-temperature alloy are austenite, Ni3Al phase, MX-type carbonitride and M 23 C6 phase.

[0029] Typically, but not limiting, the composition of the nickel-iron-based high-temperature alloy is: Cr: 15-20%, C: 0.02-0.1%, B: 0-0.01%, Ti: 0.5-2.0%, Al: 1.0-3.5%, W: ≤1.0%, Si: ≤0.8%, Mo: 0-1.0%, Co: 0-3.0%, Zr: ≤0.8%, N: 0-0.01%, Fe: 20-40%, and the balance is Ni.

[0030] Optionally, the method for electrochemical polishing of a nickel-iron-based high-temperature alloy comprises the following steps:

[0031] Pretreatment: cutting, grinding and cleaning of high temperature alloys;

[0032] Polishing treatment: Use the pre-treated high-temperature alloy as the positive electrode and enter it into the electrochemical polishing solution for electrochemical polishing.

[0033] Optionally, at least one of the following (1)-(6) is satisfied:

[0034] (1) The density of electrochemical polishing is 20 to 45 A / dm2 , polishing time is 3min~5min;

[0035] (2) The polishing step uses stainless steel as the cathode;

[0036] (3) The area ratio of stainless steel to high temperature alloy is (2-2.5):1;

[0037] (4) The inter-electrode distance between stainless steel and high-temperature alloy is 303-50mm;

[0038] (5) stirring the electrochemical polishing liquid during the polishing process at a stirring speed of 400-800 r / min;

[0039] (6) A cleaning step is also included after the polishing process.

[0040] The technical solution of the present invention has the following advantages:

[0041] The electrochemical polishing liquid provided by the present invention comprises the following components by volume: 20-60 parts of phosphoric acid; 1-3 parts of hydrochloric acid; 1-30 parts of glycerol; 10-20 parts of ethylene glycol; 15-20 parts of ethanol; the electrochemical polishing liquid also comprises naphthalenesulfonic acid at a concentration of 0.02-1g / L; and 0.02-1g / L of butynediol. The electrochemical polishing liquid provided by the present invention is particularly suitable for nickel-iron-based high-temperature alloys. It is well known in the art that nickel-iron-based high-temperature alloys have high hardness and high corrosion resistance. Other polishing methods such as mechanical polishing and chemical polishing are costly and have poor polishing effects. Moreover, nickel has a high reduction potential, and it is difficult to obtain a workpiece with low surface roughness by using conventional polishing liquid for electrochemical polishing. In the electrochemical polishing liquid provided by the present invention, naphthalenesulfonic acid, butynediol, and ethanol are organically combined with specific polyols and acids, and their synergistic effect can effectively polish the nickel-iron-based high-temperature alloy, effectively reduce the surface roughness of the alloy, and improve the surface flatness and reflectivity. In particular, ethanol is not a conventional component in polishing liquid. The present invention discovers for the first time that the use of ethanol can promote the discharge of bubbles during the polishing process, increase the uniformity of polishing, and effectively reduce the surface roughness of the alloy. In addition, the electrochemical polishing liquid provided by the present invention has a low content of oxidizing acid and contains a small amount of non-oxidizing acid. The electrochemical polishing liquid has strong stability, can be used repeatedly, and is not easy to age.

[0042] The electrochemical polishing liquid provided by the present invention has suitable fluidity and improves the dispersion ability of the solution by selecting each component and adjusting the dosage, thereby increasing the polishing speed. This is because in conventional acid electrochemical polishing liquids, the acid and polyol components generally make the solution viscosity larger, which reduces the electrochemical polishing speed.

[0043] The preparation method of the electrochemical polishing liquid provided by the present invention allows the components of the electrochemical polishing liquid to be fully dissolved and evenly mixed by limiting the mixing order, mixing speed and stirring steps. The obtained electrochemical polishing liquid has good stability and is not prone to precipitates when left for a long time, thereby improving the service life.

[0044] The electrochemical polishing liquid provided by the present invention has high polishing efficiency, little restriction on the shape of the sample, and no work hardening layer and internal stress exist on the surface of the sample after polishing, and shows great superiority in the field of surface finishing for controlling the surface quality and smoothness of nickel-iron based alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 is a surface morphology of the alloy after electrochemical polishing in Example 1 of the present invention;

[0047] Figure 2 is a line roughness measurement curve of the alloy surface along the x direction after electrochemical polishing in Example 1 of the present invention;

[0048] Figure 3 is the measurement result of the surface roughness of the alloy after electrochemical polishing in Example 1 of the present invention;

[0049] Figure 4 is a surface morphology of the alloy after electrochemical polishing in Example 2 of the present invention;

[0050] Figure 5 is a line roughness measurement curve of the alloy surface along the x direction after electrochemical polishing in Example 2 of the present invention;

[0051] Figure 6 is the measurement result of the surface roughness of the alloy after electrochemical polishing in Example 2 of the present invention;

[0052] Figure 7 This is a surface morphology of the alloy after electrochemical polishing in Comparative Example 1 of the present invention;

[0053] Figure 8 This is a measurement curve of the line roughness of the alloy surface along the x direction after electrochemical polishing in Comparative Example 1 of the present invention;

[0054] Fig. 9This is the measurement result of the surface roughness of the alloy after electrochemical polishing in Comparative Example 1 of the present invention;

[0055] Fig.10 This is a surface morphology of the alloy after electrochemical polishing in Comparative Example 2 of the present invention;

[0056] Fig.11 This is a surface morphology of the alloy after electrochemical polishing in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0057] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0058] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0059] Example 1

[0060] This embodiment provides a nickel-iron-based high-temperature alloy electrochemical polishing solution and its application, which are as follows:

[0061] First, prepare the electrochemical polishing liquid, mix 5L phosphoric acid (AR grade, ≥85wt%) and 0.2L hydrochloric acid (ACS grade, 37%), then add 0.3g of naphthalenesulfonic acid and 0.3g of butynediol respectively, and stir the above components evenly to obtain component A; add 1.8L glycerol and 1.5L ethylene glycol to 1.5L anhydrous ethanol in turn and stir evenly to obtain component B; slowly add component B to component A within 1min, and then place it on a magnetic stirrer and stir for 1h to obtain a stable electrochemical polishing liquid. After testing, the pH value of the electrochemical polishing liquid with a cycle time of about 10,000 hours did not change significantly, and it still had a good electrochemical polishing effect. Therefore, it is believed that the polishing liquid has good stability, is not easy to age, and has a long life (the results of other embodiments are similar and will not be repeated).

[0062] The nickel-iron-based high-temperature alloy (purchased from Zhejiang Jiuli Special Materials Technology Co., Ltd., the same below) was pretreated: the sample was taken with a wire cutting machine, and the alloy surface was mechanically polished step by step with 80#, 400#, 800#, 1200#, and 2000# metallographic sandpaper from low to high mesh. Then the high-temperature alloy sample was placed in acetone and anhydrous methanol solution in turn, and ultrasonically cleaned for 10 minutes each.

[0063] Polishing treatment: Connect the negative electrode of the power supply of the polishing experimental device to the stainless steel sheet, and the positive electrode of the power supply to the pre-treated nickel-iron-based high-temperature alloy. The ratio of the stainless steel electrode area to the anode nickel-iron-based high-temperature alloy area is 2.5:1, and the inter-electrode spacing is 40mm. Turn on the power supply for electrochemical polishing. The polishing current density is 30A / dm 2 ,The polishing time is 5min. The polished nickel-iron-based high-temperature alloy is repeatedly cleaned in deionized water, dehydrated with alcohol and blown dry.

[0064] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing. Figure 1 As shown in the figure, it can be seen that the alloy surface has a high flatness. The line roughness of the sample is measured along the x direction, and the curve is as follows Figure 2 shown. Figure 3 The statistical results of five groups of line roughness are shown, and it can be seen that the line roughness Ra of the alloy surface obtained in this embodiment is 0.035 um.

[0065] Example 2

[0066] This embodiment provides a nickel-iron-based high-temperature alloy electrochemical polishing solution and its application, which are as follows:

[0067] First, an electrochemical polishing solution was prepared by mixing 5 L of phosphoric acid (AR grade, ≥85 wt%) and 0.2 L of hydrochloric acid (ACS grade, 37%), and then adding 0.3 g of naphthalenesulfonic acid and 0.3 g of butynediol respectively, and stirring the above components evenly to obtain component A; 1.8 L of glycerol and 1.5 L of ethylene glycol were successively added to 1.5 L of anhydrous ethanol and stirred evenly to obtain component B; component B was slowly added to component A within 1 min, and then placed on a magnetic stirrer and stirred for 1 h to obtain a stable electrochemical polishing solution.

[0068] Pretreatment of nickel-iron-based high-temperature alloy: Samples were taken with a wire cutting machine, and the alloy surface was mechanically polished step by step with metallographic sandpapers of 80#, 400#, 800#, 1200#, and 2000# from low to high mesh. Then the high-temperature alloy samples were placed in acetone and anhydrous methanol solutions in turn, and ultrasonically cleaned for 10 minutes each.

[0069] Polishing treatment: Connect the negative electrode of the power supply of the polishing experimental device to the stainless steel sheet, and the positive electrode of the power supply to the pretreated nickel-iron-based high-temperature alloy. The ratio of the stainless steel electrode area to the anode nickel-iron-based high-temperature alloy area is 2.5:1, and the inter-electrode spacing is 40mm. Turn on the power supply for electrochemical polishing. The polishing current density is 40A / dm 2 ,The polishing time is 4min. The polished nickel-iron-based high-temperature alloy is repeatedly cleaned in deionized water, dehydrated with alcohol and blown dry.

[0070] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing. Figure 3 As shown in the figure, it can be seen that the alloy surface has a high flatness. The line roughness of the sample is measured along the x direction, and the curve is as follows Figure 5 shown. Figure 6 The statistical results of five groups of line roughness are shown, and it can be seen that the line roughness Ra of the alloy surface obtained in this embodiment is 0.054 um.

[0071] Example 3

[0072] This embodiment provides a nickel-iron-based high-temperature alloy electrochemical polishing solution and its application, which are as follows:

[0073] First, an electrochemical polishing solution was prepared by mixing 4 L of phosphoric acid (AR grade, ≥85 wt%) and 0.2 L of hydrochloric acid (ACS grade, 37%), and then adding 0.3 g of naphthalenesulfonic acid and 0.3 g of butynediol respectively, and stirring the above components evenly to obtain component A; 2.3 L of glycerol and 2 L of ethylene glycol were successively added to 1.5 L of anhydrous ethanol and stirred evenly to obtain component B; component B was slowly added to component A within 1 min, and then placed on a magnetic stirrer and stirred for 1 h to obtain a stable electrochemical polishing solution.

[0074] Pretreatment of nickel-iron-based high-temperature alloy: Samples were taken with a wire cutting machine, and the alloy surface was mechanically polished step by step with metallographic sandpapers of 80#, 400#, 800#, 1200#, and 2000# from low to high mesh. Then the high-temperature alloy samples were placed in acetone and anhydrous methanol solutions in turn, and ultrasonically cleaned for 10 minutes each.

[0075] Polishing treatment: Connect the negative pole of the power supply of the polishing experimental device to the stainless steel sheet, and the positive pole of the power supply to the pretreated nickel-iron-based high-temperature alloy. The ratio of the stainless steel electrode area to the anode nickel-iron-based high-temperature alloy area is 2.5:1, and the inter-electrode spacing is 30mm. Turn on the power supply for electrochemical polishing. The polishing current density is 35A / dm 2 ,The polishing time is 5min. The polished nickel-iron-based high-temperature alloy is repeatedly cleaned in deionized water, dehydrated with alcohol and blown dry.

[0076] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing, and the alloy surface flatness was high. The line roughness of the sample was measured, and the statistical results showed that the surface line roughness Ra of the alloy obtained in this embodiment was 0.046 um.

[0077] Example 4

[0078] This embodiment provides a nickel-iron-based high-temperature alloy electrochemical polishing solution and its application, which are as follows:

[0079] First, an electrochemical polishing solution was prepared by mixing 4 L of phosphoric acid (AR grade, ≥85 wt%) and 0.2 L of hydrochloric acid (ACS grade, 37%), and then adding 0.3 g of naphthalenesulfonic acid and 0.3 g of butynediol respectively, and stirring the above components evenly to obtain component A; 2.3 L of glycerol and 2 L of ethylene glycol were successively added to 1.5 L of anhydrous ethanol and stirred evenly to obtain component B; component B was slowly added to component A within 1 min, and then placed on a magnetic stirrer and stirred for 1 h to obtain a stable electrochemical polishing solution.

[0080] Pretreatment of nickel-iron-based high-temperature alloy: Samples were taken with a wire cutting machine, and the alloy surface was mechanically polished step by step with metallographic sandpapers of 80#, 400#, 800#, 1200#, and 2000# from low to high mesh. Then the high-temperature alloy samples were placed in acetone and anhydrous methanol solutions in turn, and ultrasonically cleaned for 10 minutes each.

[0081] Polishing treatment: Connect the negative pole of the power supply of the polishing experimental device to the stainless steel sheet, and the positive pole of the power supply to the pre-treated nickel-iron-based high-temperature alloy. The ratio of the stainless steel electrode area to the anode nickel-iron-based high-temperature alloy area is 2.5:1, and the inter-electrode spacing is 30mm. Turn on the power supply for electrochemical polishing. The polishing current density is 40A / dm 2 ,The polishing time is 3min. The polished nickel-iron-based high-temperature alloy is repeatedly cleaned in deionized water, dehydrated with alcohol and blown dry.

[0082] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing, and the alloy surface flatness was high. The line roughness of the sample was measured, and the statistical results showed that the surface line roughness Ra of the alloy obtained in this embodiment was 0.050 um.

[0083] Example 5

[0084] This embodiment provides a nickel-iron-based high-temperature alloy electrochemical polishing liquid and its application. Compared with Example 1, the only difference is that the composition of the electrolytic polishing liquid is different. The specific composition is as follows:

[0085] First, an electrochemical polishing solution was prepared by mixing 2L phosphoric acid (AR grade, ≥85wt%) and 0.1L hydrochloric acid (ACS grade, 37%), and then adding 0.26g naphthalenesulfonic acid and 0.26g butynediol respectively, and stirring the above components evenly to obtain component A; 0.1L glycerol and 1L ethylene glycol were successively added to 2L anhydrous ethanol and stirred evenly to obtain component B; component B was slowly added to component A within 2 minutes, and then placed on a magnetic stirrer and stirred for 1 hour to obtain a stable electrochemical polishing solution.

[0086] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing, and the alloy surface flatness was high. The line roughness of the sample was measured, and the statistical results showed that the surface line roughness Ra of the alloy obtained in this embodiment was 0.042 um.

[0087] Example 6

[0088] This embodiment provides a nickel-iron-based high-temperature alloy electrochemical polishing liquid and its application. Compared with Example 1, the only difference is that the composition of the electrolytic polishing liquid is different. The specific composition is as follows:

[0089] First, an electrochemical polishing solution was prepared by mixing 6L phosphoric acid (AR grade, ≥85wt%) and 0.3L hydrochloric acid (ACS grade, 37%), and then adding 10g naphthalenesulfonic acid and 10g butynediol respectively, and stirring the above components evenly to obtain component A; 3L glycerol and 2L ethylene glycol were successively added to 1.8L anhydrous ethanol and stirred evenly to obtain component B; component B was slowly added to component A within 2min, and then placed on a magnetic stirrer and stirred for 1h to obtain a stable electrochemical polishing solution.

[0090] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing, and the alloy surface flatness was high. The line roughness of the sample was measured, and the statistical results showed that the surface line roughness Ra of the alloy obtained in this embodiment was 0.030 um.

[0091] Comparative Example 1

[0092] This comparative example provides a nickel-iron-based high-temperature alloy electrochemical polishing liquid and its application, which is different from Example 1 only in that glycerol is used instead of ethanol in the electrolytic polishing liquid.

[0093] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing. Figure 7 As shown, the line roughness of the sample is measured along the x direction, and the curve is as follows Figure 8 As shown in the figure, it can be seen that the alloy surface has obvious depressions and protrusions, and the leveling effect is not good. The surface line roughness of the alloy obtained in this embodiment is as follows Fig. 9 As shown, its Ra is 0.079um.

[0094] Comparative Example 2

[0095] This comparative example provides a nickel-iron-based high-temperature alloy electrochemical polishing liquid and its application. The only difference from Example 1 is that 37% nitric acid is used instead of hydrochloric acid in the electrolytic polishing liquid. After testing, the pH value of the electrochemical polishing liquid with a cycle time of about 10,000 hours changes significantly, and the electrochemical polishing effect becomes worse. Therefore, it is believed that the polishing liquid has poor stability, is easy to age, and has a short life.

[0096] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing. Fig.10 As shown in the figure, it can be seen that the corrosion degree of the alloy surface is uneven and cannot meet the polishing requirements.

[0097] Comparative Example 3

[0098] This comparative example provides a nickel-iron-based high-temperature alloy electrochemical polishing liquid and its application, which is different from Example 1 only in that naphthalenesulfonic acid is not included in the electrolytic polishing liquid.

[0099] Laser confocal microscopy was used to observe the surface morphology of the alloy after electrochemical polishing. Fig.11 As shown in the figure, it can be seen that the alloy surface has obvious depressions and protrusions, the leveling effect is poor, and it cannot meet the polishing requirements.

[0100] Comparative Example 4

[0101] This comparative example provides a nickel-iron-based high-temperature alloy electrochemical polishing solution and its application. Compared with Example 1, the only difference is that the phosphoric acid in the electrolytic polishing solution is adjusted from 5L to 4.8L, and the hydrochloric acid is adjusted from 0.2L to 0.4L.

[0102] In this comparative example, the hydrochloric acid content is relatively high, and the alloy surface is excessively corroded, which cannot meet the polishing requirements.

[0103] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A nickel-iron-based high-temperature alloy electrochemical polishing solution, characterized in that: By volume, it includes the following components: Phosphoric acid 20-60 parts; hydrochloric acid 1-3 parts; glycerol 1-30 parts; ethylene glycol 10-20 parts; ethanol 15-20 parts; The electrochemical polishing solution also includes naphthalenesulfonic acid at a concentration of 0.02-1 g / L and butynediol at a concentration of 0.02-1 g / L.

2. The nickel-iron-based high-temperature alloy electrochemical polishing liquid according to claim 1, characterized in that: By volume, it includes the following components: Phosphoric acid 40-60 parts; hydrochloric acid 2-3 parts; glycerol 18-30 parts; ethylene glycol 15-20 parts; ethanol 15-20 parts; The electrochemical polishing solution also includes naphthalenesulfonic acid at a concentration of 0.03-1 g / L and butynediol at a concentration of 0.03-1 g / L.

3. The nickel-iron-based high-temperature alloy electrochemical polishing liquid according to claim 1 or 2, characterized in that: The mass concentration of the phosphoric acid is above 85wt%; And / or, the mass concentration of the hydrochloric acid is above 37wt%.

4. The nickel-iron-based high-temperature alloy electrochemical polishing liquid according to any one of claims 1 to 3, characterized in that: The viscosity of the electrochemical polishing liquid at 25° C. is 100-200 mP·s.

5. A method for preparing the nickel-iron-based high-temperature alloy electrochemical polishing liquid according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing phosphoric acid and hydrochloric acid, adding naphthalenesulfonic acid and butynediol to obtain component A; S2, adding glycerol and ethylene glycol to ethanol in sequence to obtain component B; S3, mixing component A and component B, stirring to obtain the electrochemical polishing solution.

6. The method for preparing the nickel-iron-based high-temperature alloy electrochemical polishing liquid according to claim 5, characterized in that: Keep stirring while mixing Part A and Part B.

7. The method for preparing the nickel-iron-based high-temperature alloy electrochemical polishing liquid according to claim 5, characterized in that: The stirring time is 0.5-1h.

8. Use of the nickel-iron-based high-temperature alloy electrochemical polishing liquid according to any one of claims 1 to 4 or the nickel-iron-based high-temperature alloy electrochemical polishing liquid prepared by the preparation method according to any one of claims 5 to 7 in electrochemical polishing of high-temperature alloys.

9. The use according to claim 8, characterized in that: The method for electrochemical polishing of nickel-iron-based high-temperature alloy comprises the following steps: Pretreatment: cutting, grinding and cleaning of high temperature alloys; Polishing treatment: Use the pre-treated high-temperature alloy as the positive electrode and enter it into the electrochemical polishing solution for electrochemical polishing.

10. The use according to claim 9, characterized in that: Satisfy at least one of the following (1)-(6): (1) The density of electrochemical polishing is 20 to 45 A / dm 2 , polishing time is 3min~5min; (2) The polishing step uses stainless steel as the cathode; (3) The area ratio of stainless steel to high temperature alloy is (2-2.5):1; (4) The inter-electrode distance between stainless steel and high-temperature alloy is 303-50mm; (5) stirring the electrochemical polishing liquid during the polishing process at a stirring speed of 400-800 r / min; (6) A cleaning step is also included after the polishing process.

Citation Information

Patent Citations

  • Electrochemical polishing liquid and polishing method for laser additive-manufactured specially-shaped titanium alloy

    CN108360059A

  • electrochemical treatment process

    DE2834946A1